ANALISIS HUTANG KINERJA KEUANGAN DAN KINERJA OPERASIONAL PDAM KABUPATEN BANYUMAS - Sri Lestari (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
The aims of this study are to investigate and analyze the debt condition, debt management performance, financial performance, and operational performance of Water Supply Company in Banyumas Regency. This study uses descriptive method and financial ratio to analyze debt management performance, and also the ratio according to Keputusan Menteri Perdagangan Republik Indonesia No. 47 Tahun 1999 in order to measure financial and operational performance of Water Supply Company in Banyumas Regency. The data used in this study is quantitative data of Water Supply Company from 2005-2009. The result of this study indicates that along the research period, the Water Supply Company is not charged by long debt. The asset of Water Supply Company in Banyumas Regency is more than their capital. The result shows that financial performance of Water Supply Company in Banyumas Regency is good, and their operational performance is good enough. This study gives the implication to Water Supply Company in Banyumas Regency to keep and increase their performance to better performance.